Design of experiments-assisted UPLC method for quantification of nitrosamine impurities in glimepiride and lobeglitazone sulfate: A green chemistry approach - KiranKumar Chagarlamudi; Venkata Kanaka Srivani Maddala; Kumaraswamy Gandla (Journal of Pharmaceutical and Biomedical Analysis Open)
A robust ultra-performance liquid chromatography (UPLC) method was developed and systematically optimized using a Design of Experiments (DoE) approach for the simultaneous quantification of glimepiride, lobeglitazone sulfate, nitrosamine impurity-3 (IMP-3), and impurity-1 (IMP-1) in the marketed LOBG-G1 formulation. Critical method parameters, including organic phase composition, flow rate, and mobile phase pH, were identified through a comprehensive risk assessment and subsequently optimized using a Box-Behnken design. The final chromatographic conditions—50 % organic phase composition, a flow rate of 0.2 mL/min, and a mobile phase pH of 2.6—ensured efficient separation and quantification of all four analytes. The method was validated in accordance with ICH guidelines, demonstrating excellent linearity (r² > 0.999), high accuracy, and precision, with low relative standard deviation values. Stability studies conducted under different stress conditions revealed significant degradation of all four compounds in acidic, alkaline, and oxidative environments. Degradation products were further characterized using LC-MS/MS analysis, confirming their structural identity. In addition to its analytical performance, the method's environmental sustainability was evaluated using multiple green analytical chemistry assessment tools. The DoE-guided UPLC method offers a highly sensitive, selective, and reproducible analytical platform for the detection of nitrosamine impurities in antidiabetic drugs, providing enhanced method understanding while aligning with sustainability principles.